Hagiographie et théorie mimétique - Julia Sei (Carnets)
The Martyrs of Lyons and Vienne, preserved in Eusebius’ Ecclesiastical History, book V, describes one of the cruelest persecutions to be executed against the early Church. The letter relates how, in the absence of a governor, in 177, an infuriated mob clamored for the massacre of the Christian community. I am aiming to show how mimetic theory casts a new light on hagiography as a literary genre. The Martyrs of Lyons perfectly corresponds to the Girardian definition of the scapegoat, and unites all of Girard’s stereotypes of persecution. The scapegoat/martyr is channeling collective violence and thus regulates the community’s internal tensions. I will aim for a hermeneutics of hagiography in which the evangelic sphere reveals the depth of sacrificial violence. A new aspect of hagiographical texts can be unravelled with a Girardian reading.31 janvier 2018